Understanding social media and its influence on interpersonal communication and behaviour among Malaysian youths - Lim, Lucas Ye-Kai (2023)
With the advent of technology, the communication aspect of it has taken a big leap. Gone are the days where messages would take a while to write and deliver. The improvement of technology has also brought about powerful handheld devices capable of connecting everyone from all walks of life together through the Internet. This was done through the development of social media platforms which allow its users to share varying information like pictures and videos and exchange conversations. Social media was in its purest form during the early years. As time passed and with the increasing accessibility of technology, everyone was more connected than they were before. While the maturing of social media seems objectively good on paper, it has also brought a wave of negative effects. Time and time again we’ve seen news articles shining light on the effects social media has on its users, particularly how the younger demographic is suffering from mental illnesses or loneliness. Such a phenomenon can be attributed to the modern age of social media being a platform for people to only show the positive side of their lives, which causes a negative chain reaction for those unaware of the illusion. However, there is a lack of information about this phenomenon in Malaysia as most of the vocal demographic exists in the Western countries. This research conducted using a quantitative method among Malaysian youths aged 15 to 24 which aims to delve into detail on how social media in the modern age has influenced Malaysian youths’ interpersonal communication skills and perception towards social media, and also to shine light on how social media has changed over the course of its development.